Exercise and diet studies among patients living with multiple myeloma: current evidence and considerations of patient preferences - Maslana, Kelsey E.; Skogerboe, Grace E.; Sborov, Douglas W.; Coletta, Adriana M. (Frontiers in Hematology, 2025)
BackgroundMultiple myeloma (MM) is the second most common blood cancer after leukemia in adults. Despite advancements in treatment that have extended survival, MM remains incurable and the cancer and its treatment result in adverse acute, long-term and latent side-effects, necessitating a focus on strategies to attenuate these side-effects and improve quality of life. This narrative review highlights MM patient preferences for exercise and/or diet interventions relative to complete and ongoing interventions to identify gaps and needs for future lifestyle interventions in MM patients aimed at improving MM survivorship care.MethodsThis updated review was completed using a comprehensive search that was conducted using PubMed and ClinicalTrials.gov databases using keywords related to MM, exercise, physical activity, diet, nutrition and patient preferences. Studies involving adults diagnosed with MM were included.ResultsAmong published studies, there are five exercise interventions and four diet and nutrition observational studies. The importance of individualized exercise interventions tailored to MM patients’ needs was emphasized. Supervised exercise interventions showed higher adherence and engagement compared to unsupervised interventions. Observational diet/nutrition studies demonstrated that decreased gut microbiome diversity post-transplant is linked to poorer outcomes. Additionally, nutritional status and dietary patterns, such as high-carbohydrate and plant-based diets, can significantly impact clinical outcomes in MM patients, including sustained minimal residual disease negativity. Current clinical trials are primarily focused on feasibility and adherence, with a limited emphasis on long-term outcomes. In ClinicalTrials.gov, there are six ongoing exercise interventions, with an additional seven that are completed with no published results, one suspended trial and one active but not recruiting. Additionally, there are two combined diet and exercise interventions that are currently recruiting, with one active but no longer recruiting. Among diet and nutrition ongoing trials, there are currently two actively recruiting, two completed with no primary paper published and one study that was withdrawn.DiscussionThese findings underscore the need for more comprehensive, long-term and adequately powered studies on the impact of exercise and diet interventions in MM patients. Patient education and empowerment within these trials are crucial for enhancing engagement and adherence to these interventions.